Empowering Young Women with Polycystic Ovary Syndrome through Food and Nutrition Literacy - Mathema, Sujala; Aryal, Bhagwan; Subedi, Sibila (Journal of Health Promotion, 2024)
Literature on Polycystic Ovary Syndrome (PCOS) suggests that women with PCOS have a higher prevalence of disordered eating behaviors, such as restrictive dieting and binge eating, and clinical eating disorders, compared to women without PCOS. Diet and nutrition are crucial for symptom control and lifestyle changes, including active lifestyle and dietary patterns. A comprehensive study on Food and Nutrition Literacy (FANLit) among women with PCOS and relevant healthcare organizations is yet to be fully explored. This study followed the PRISMA methodology to guide the review process and to explore FANLit in women with PCOS and the role of healthcare organizations in providing care and support. The findings show that adhering to healthy dietary principles, such as low low-calorie, low-glycemic diet, combined with lifestyle modifications, sleep improvement, and physical activity can help women with PCOS manage their physiological homeostasis and recover effectively. An integrated therapeutic approach is essential to reduce metabolic symptoms associated with PCOS. Improved nutritional literacy empowers women with PCOS to utilize food as a key strategy for symptom management, reducing reliance on medications. However, gaps in Health Literacy (HL) persist, as evidenced by the findings from this review. Functional HL issues include unsupported weight loss attempts and limited dietitian referrals, while interactive HL highlights the need for improved communication between healthcare professionals and patients, diagnostic clarity, and more tailored resources. These conclusions are derived from this PRISMA-guided scoping review that systematically analyzed relevant literature to map current knowledge and identify gaps in HL and FANLit for women with PCOS.